NOx Formation in MILD Combustion: Potential and Limitations of Existing Approaches in CFD - Iavarone, Salvatore; Parente, Alessandro (Frontiers in Mechanical Engineering, 2020)
Emissions of nitrogen oxides (NOx) from combustion systems remain a lingering environmental issue, being these species either greenhouse gases or acid rain precursors. Moderate or Intense Low-oxygen Dilution (MILD) combustion can reduce the emissions of nitrogen oxides thanks to its characteristic features (i.e., homogeneous reaction zones, reduced temperature peaks, diluted mixtures of reactants) that influence and change the main chemical pathways of NOx formation. A summary of the relevant routes of formation and destruction of nitrogen oxides in MILD combustion is presented in this review, along with the identification of the sources of uncertainty that prevent reaching an overall consensus in the literature about the dominant NOx chemical pathway in MILD regime. Computational Fluid Dynamics (CFD) approaches are essential tools for investigating the critical phenomena occurring in MILD combustion and the design of pollutant-free turbulent combustion systems. This paper provides an outline of the modeling approaches employed in CFD simulations of turbulent combustion systems to predict NOx emissions in MILD conditions. An assessment of the performances of selected models in estimating NOx formation in a lab-scale MILD combustion burner is then presented, followed by a discussion about relevant modeling issues, perspectives and opportunities for future research.